2021
DOI: 10.3390/s21062222
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Brain Tumor Classification Using Ensemble of Deep Features and Machine Learning Classifiers

Abstract: Brain tumor classification plays an important role in clinical diagnosis and effective treatment. In this work, we propose a method for brain tumor classification using an ensemble of deep features and machine learning classifiers. In our proposed framework, we adopt the concept of transfer learning and uses several pre-trained deep convolutional neural networks to extract deep features from brain magnetic resonance (MR) images. The extracted deep features are then evaluated by several machine learning classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
140
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(178 citation statements)
references
References 67 publications
(54 reference statements)
0
140
0
Order By: Relevance
“…A leaf node of tree represents the record set corresponding to the leaf node of decision tree under certain conditions. The decision tree is generated by repeatedly establishing lower-level nodes in branch subsets [12]. CART is a typical binary decision tree, which can do both classification and regression.…”
Section: Mineral Resource Prediction By Amentioning
confidence: 99%
“…A leaf node of tree represents the record set corresponding to the leaf node of decision tree under certain conditions. The decision tree is generated by repeatedly establishing lower-level nodes in branch subsets [12]. CART is a typical binary decision tree, which can do both classification and regression.…”
Section: Mineral Resource Prediction By Amentioning
confidence: 99%
“…However, the training time of the pre-trained network was very high. To tackle this issue, Kang et al [ 26 ] computed the feature of brain images using pre-trained networks and trained the classical classifier. They found that the ensemble features computed using DenseNet-169, ShuffleNet V2, and MnasNet with the SVM had the best testing accuracy of 93.72% for four classes (no tumor, glioma, meningioma, and pituitary).…”
Section: Introductionmentioning
confidence: 99%
“…The different types of features include texture, brightness, contrast, shape, Gabor transforms, gray-level co-occurrence matrix (GLCM), and wavelet-based features [ 115 , 120 ], histogram of local binary patterns (LBP) [ 121 ]. On the other hand, recently, deep features that are obtained from deep neural networks such as CNN have been used as input to SVM classifier to classify brain tumors [ 122 ]. In brain tumor classification, it is customary to fuse several features from different extraction models to improve the discrimination power of the machine learning model [ 123 ].…”
Section: Brain Tumor Classification Methodsmentioning
confidence: 99%
“…Different classification techniques have been proposed by many authors for identifying tumor types from brain images. Different authors have classified tumor into a variety of ways, for instance meningioma, glioma, and pituitary [ 109 , 121 , 122 , 124 , 125 ]; astrocytoma, glioblastoma, and oligodendrogliamo [ 112 ]; glioma tumor grades (I–IV) [ 113 ]; benign and malignant stages(I–IV) [ 126 , 127 , 128 , 129 ]; diffuse midline glioma, medulloblastoma, pilocytic astrocytoma, and ependymoma [ 102 ]; multifocal, multicentric, and gliomatosis [ 130 ]; ependymoma and pilocytic astrocytoma [ 120 ].…”
Section: Brain Tumor Classification Methodsmentioning
confidence: 99%
See 1 more Smart Citation